ERIC- PCRisan adequate tool for typing of clinical Pseudomonas aeruginosa isolates - ALmusawi, Duaa (International Journal of Psychosocial Rehabilitation, 2020)
In this study, the ERIC- PCR fingerprinting technique was evaluated for the discrimination of clinical Pseudomonas aeruginosa isolates. All isolates except 4 were type able and some isolates showed unique banding patterns. According to our results, ERIC-PCR fingerprinting is applicable for typing of Pseudomonas aeruginosa isolates and can be considered a useful complementary tool for epidemiological studies of members of this genus.